Philosophical-anthropological and historical-cultural aspects of the educational activities of Kh.D. Alchevska (to the 185th anniversary of her birth) - Tytar, Olena; Fradkinа, Natalya (Вісник гуманітарних наук, 2025)
The article offers a comprehensive philosophical and historical-cultural analysis of the activities of Khrystyna Danylivna Alchevska (1841–1920) as one of the key figures of the Ukrainian and Eastern European public education movements. The purpose of the work is to study the philosophical-anthropological dimension of Khrystyna Alchevska's pedagogical concepts, the historical-cultural aspects of the emergence of Alchevska's educational views and their spread. Methods. An interdisciplinary approach was applied, combining historical and philosophical anthropology, historical-cultural and biographical methods. The key methodology of the study is the history and philosophy of Ukrainian education. The article uses a complex interdisciplinary approach that combines three methodological frameworks: hermeneutic, historical, cultural and philosophical and anthropological. This combination is substantiated by the specifics of the source base (memoirs, pedagogical texts, bibliographic indexes) and the very nature of the phenomenon of Christina Alchevska’s activity, which is at the intersection of the history of education, social history and philosophy of culture. Results. The intellectual origins of her approaches, the organizational model of the Kharkiv Women’s Sunday School (1862–1919), the concept of «reading as a thinking activity», as well as two basic corpuses of texts, namely «The Book of Adults» and the three-volume index «What to Read to the People?» are considered. Based on memoirs, program documents, and modern historiography, the philosophy of education of Alchevska, its ethical and anthropological principles, gender dimension, and socio-political limitations of the imperial context are reconstructed. In particular, the project of Khrystyna Alchevska’s Sunday schools and the activities of the New Ukrainian School and adult education (andragogy) are compared: from the pedagogy of partnership and public schools to interpretive practices of reading, media literacy, and bibliotherapy. Conclusions. It is shown that the key ideas of Khrystyna Alchevska’s education are surprisingly well-consonant with the New Ukrainian School (NUS) and the ideas of global education throughout life (adult education). The basis of Khrystyna Alchevska’s Sunday schools and the modern school is the pedagogy of partnership, based on trust and dialogue. The community discovers its educational potential in Alchevska’s activities, which are realized through open libraries and reading clubs, where education builds a «house of shared meanings». Important are such interpretative reading practices discovered by Khrystyna Danylovna as «reading with explanations», which becomes a method of forming critical thinking, and evidence-based selection of content with the help of local councils with the participation of students and librarians. It is shown that the educational paradigm of Kh.D. Alchevska offers not only a vivid historical example, but also a methodology of national stability, where trust, work of thought, evidence-based selection of cultural content, and democracy are the basis of the school. In today's context, especially in the New Ukrainian School, adult education and postgraduate training, these principles enhance school autonomy, promote quality reading, and ground education in human dignity.